Pengaruh Gaya Hidup Pada Wanita Pekerja Pabrik Dan Bukan Pekerja Pabrik Terhadap Hipertensi Pada Usia 40-60 Tahun - mawar, mawar; Waskito, Budi Arief; Soekanto, Ayly (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2025)
Introduction: As time goes by, women's work is not only centered at home, but also they are involved in activities outside the home such as working. Working and non-working women have different lifestyles and can be directly or indirectly exposed to risk factors that can cause hypertension. Because of this phenomenon, the authors want to examining effect lifestyle on women who work in factories and women who are not factory workers on hypertension in the 40-60 Year Age Group in the January - March 2024 Period in Sidokepung Village, Sidoarjo. Methods: This study is a quantitative approach with a cross-sectional design and qualitative in the form of interviews. The study population was workers and not factory workers with an age group of 40-60 years in Sidokepung Village, Sidoarjo with a sample taken for this study of 60 workers who met the inclusion and exclusion criteria, and analysis with Chi Square test. Results: Most of the respondents who worked as factory workers, experienced hypertension. The risk factors for hypertension are mostly due to risk factors for physical activity. Other risk factors that researchers raised in this study such as risk factors for high salt diet, stress, and obesity not association with hypertension in factory workers in Sidokepung Village, Sidoarjo. Conclusion: The results showed that hypertension was higher in women factory workers in Sidokepung Village, Sidoarjo, where the risk factor for hypertension in women factory workers in Sidokepung Village, Sidoarjo was physical activity.